INFLUENCE OF ALBASIA WOOD ON MECHANICAL PROPERTIES AND MORPHOLOGY OF EPOXY COMPOSITES - Pratiwi, Henny (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2018)
This research aims to investigate the effects of albasia wood filler as alternative reinforcement for extravagant and non-renewable filler being used in epoxy composites. The filler size used was 30 mesh and various filler volume fractions were 10, 20, 30 and 40 percent. Composites were manufactured using hand lay-up method. Properties such as tensile strength, elongation, modulus elasticity and strain energy absorption were determined based on ASTM standard. The results show that filler volume content significantly affects the tensile properties and impact strength of albasia wood-epoxy composites. The optimum tensile properties are achieved when 10 percent filler is added into epoxy matrix. The impact test also shows the same results. Further addition of filler decreases the mechanical properties of composites due to the existence of weak interfacial interaction between the albasia wood filler and polymer matrix for higher filler volume concentration beyond 10 vol. %. The scanning electron micrograph reveals that there are voids and pull-out mechanism on tensile fracture surface which are the cause of the composites failure.